Fact and Fiction in the Life Story of Luigi von Kunits. (19th December 2014) - Elliott, Robin
<x content-type="archive" xml:space="preserve">Abstract</x> Luigi von Kunits (1870–1931) had a substantial impact on classical music in Toronto. Born and educated in Vienna, he emigrated to Chicago in 1893 and then moved to Pittsburgh in 1896 as the concertmaster of the Pittsburgh Orchestra. After 17 years in the USA, he returned to Vienna for two years, before moving to Toronto to take up a teaching position at the Canadian Academy of Music. From the time of his arrival in Toronto in 1912 to his death in 1931 he was active on many fronts: teaching violin, composing, editing The Canadian Journal of Music (1914–1919), performing as a chamber musician and violin soloist, and serving as the conductor of the Toronto Symphony Orchestra (1922–1931). To many he seemed the very embodiment of the great Central European musical tradition: a pupil of Bruckner and Hanslick, associated with Brahms and acquainted with celebrated European musicians and composers. Much of what we know about Kunits derives from statements issuing from the musician himself or his immediate circle, with little or no corroborating evidence to support his assertions. As a result, it is difficult at this remove to separate fact from fiction. This article takes stock of the sources of information that are available and attempts to construct as accurate an account of his life and activities as possible.